UJI AKTIVITAS ANTIOKSIDAN DARI AMPAS HASIL PENGOLAHAN SAGU (Metroxylon sagu Rottb) - Talapessy, Selvian; Suryanto, Edi; Yudistira, Adithya (PHARMACON, 2013)
ABSTRACTThe study aimed to determine the phenolic content and antioxidant activity of sago wasteprocessing results. Results of processing sago pulp esxtraction was conducted using 1 x 24hour maceration using solvents ethanol with a concentration of 20, 40, 60 and 80%. Phenoliccontent was determined by Folin Ciocalteu method and determination of antioxidant activityusing the DPPH free radical scavengers. The results showed that the extract with the solventconcentration of 40% has a higher total phenolic 83,26 Î¼g/mL followed by solvent extractconcentration of 20, 60 and 80% respectively 70,01; 60,58; 22,04 Î¼g/mL. extract with 60%solvent concentration has free radical scavengers activity the highest of 82,75% followed byconcentration of solvent extracts 80, 20 and 60% are respectively 80,45; 76,62; 62,83%.These results suggest that the processing of sago pulp extract contains phenolic antioxidantsand can be potentially as.Keywords : pulp extract sago precessing results, phenolic compend, antioxidants.